Direct Detection of Circulating Tumor Cells in Whole Blood Using Time‐Resolved Luminescent Lanthanide Nanoprobes. (25th July 2019) - Guo, Hanhan; Song, Xiaorong; Lei, Wen; He, Cheng; You, Wenwu; Lin, Qingzhong; Zhou, Shanyong; Chen, Xueyuan; Chen, Zhuo
Abstract: The detection of circulating tumor cells (CTCs) is crucial to early cancer diagnosis and the evaluation of cancer metastasis. However, it remains challenging due to the scarcity of CTCs in the blood. Herein, we report an ultrasensitive platform for the direct detection of CTCs using luminescent lanthanide nanoprobes. These were designed to recognize the epithelial cell adhesion molecules on cancer cells, allowing signal amplification through dissolution‐enhanced time‐resolved photoluminescence (TRPL) and the elimination of short‐lived autofluorescence interference. This enabled the direct detection of blood breast‐cancer cells with a limit of detection down to 1 cell/well of a 96‐well plate. Moreover, blood CTCs (≥10 cells mL −1 ) can be detected in cancer patients with a detection rate of 93.9 % (14/15 patients). We envision that this ultrasensitive detection platform with excellent practicality may provide an effective strategy for early cancer diagnosis and prognosis evaluation. Abstract : Der direkte Nachweis von zirkulierenden Tumorzellen (CTCs) im Vollblut gelang mit zeitaufgelösten lumineszierenden Lanthanoid‐Nanosonden. Diese Strategie hat eine Nachweisgrenze von bis zu 1 Zelle/Vertiefung in einer 96er‐Titerplatte (200 μL) ohne die Notwendigkeit von Anreicherungsschritten, was eine Krebsdiagnose mit einer Nachweisrate von 93.9 % ermöglicht.